2013
DOI: 10.1292/jvms.13-0004
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates the Oxidative Damage Induced by Arsenic Trioxide in the Feline Lung

Abstract: ABSTRACT. The objective of this study was to evaluate the possible protection of resveratrol against lung injury induced by arsenic trioxide (As 2 O 3 ). Twenty-four healthy Chinese Dragon Li cats of either sex were randomly divided into four groups: control (1 ml/kg physiological saline), As 2 O 3 (1 mg/kg), resveratrol (3 mg/kg) and resveratrol (3 mg/kg) + As 2 O 3 (1 mg/kg). The resveratrol + As 2 O 3 -treated group was given resveratrol 1 hr before As 2 O 3 (1 mg/kg) administration. We found that pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…CS exposure was carried out (five cigarettes for five times a day (one cigarette/time) with 30‐min smoke‐free interval for 3 consecutive days) by burning a commercially available filter cigarette (White Shark brand, Tobacco Company, People's Republic of China) according to manufacturer's specification (1 mg nicotine/cigarette; 13 mg tar/cigarette) . Oral administration of resveratrol (1 or 3 mg/kg) or vehicle (1% DMSO in 0.1 mL phosphate buffered saline (PBS)) was given 1 h before CS treatment . Mice were anesthetized with Avertin (2,2,2‐tribromoethanol, 250 mg/kg ip; Sigma‐Aldrich, St. Louis, MO) and euthanized by exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…CS exposure was carried out (five cigarettes for five times a day (one cigarette/time) with 30‐min smoke‐free interval for 3 consecutive days) by burning a commercially available filter cigarette (White Shark brand, Tobacco Company, People's Republic of China) according to manufacturer's specification (1 mg nicotine/cigarette; 13 mg tar/cigarette) . Oral administration of resveratrol (1 or 3 mg/kg) or vehicle (1% DMSO in 0.1 mL phosphate buffered saline (PBS)) was given 1 h before CS treatment . Mice were anesthetized with Avertin (2,2,2‐tribromoethanol, 250 mg/kg ip; Sigma‐Aldrich, St. Louis, MO) and euthanized by exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…In guinea pig ventricular cardiomyocytes, resveratrol ameliorated arsenic trioxide-induced damage of the human ether-a-go-go-related gene (hERG) current, relieved endoplasmic reticulum stress, and shortened the action potential duration [171]. Resveratrol also had a protective effect against arsenic trioxide-induced oxidative damage in the feline brain, lung, and kidney [172,173,174], and nephrotoxicity and hepatotoxicity in rats [175,176].…”
Section: Other Cardiotoxic Cancer Treatmentsmentioning
confidence: 99%
“…Histopathological examination of the kidneys and bladder revealed minor inflammatory infiltrates, but these were not considered significant (Johnson et al., ). Another study in cats reported a protective effect against reactive oxygen species in cats with pulmonary exposure to arsenic (Cheng et al., ). However, to date, the authors are unaware of any metabolism and safety studies published in cats.…”
Section: Introductionmentioning
confidence: 99%